Microphthalmos with Orbital Cyst: Case series with a review of literature - Pant, Aashish Raj; Suwal, Rinkal; Joshi, Purushottam; Chaudhary, Santosh; Sharma, Sujan; Shrestha, Nisha (Birat Journal of Health Sciences, 2022)
Microphthalmos with orbital cyst is a rare congenital abnormality of fetal fissure closure leading to a small eyeball associated with an orbital cyst. In this case series, we describe six such cases and discuss the clinical features, differential diagnosis, diagnostic modalities, and management in accordance with the existing literature. Out of the six cases, four were male and two were females. All the cases presented with a swelling in the lower eyelid of the involved eye, which was the right eye in all the male patients and the left eye in all the female cases. Other eye showed uveal coloboma in 50% of the cases. Microphthalmos with orbital cyst was diagnosed based on the clinical features and radiological findings (ultrasonography B-scan and/or Computed Tomography scan). Two patients from our case series underwent surgery (cyst excision with enucleation of microphthalmic eye with orbital implant and conformer) and, histopathology confirmed the diagnosis of microphthalmos with orbital cyst. Microphthalmos with orbital cyst presents as a swelling of the lower eyelid since birth in which a careful examination often reveals a microphthalmic eye. Two such cases in our case series were managed with orbital cyst excision and enucleation of microphthalmic eye followed by orbital implant and conformer, leading to good cosmetic results.